Employability And It Competency Of Accounting Graduates In Responding To 4Ir - Zolkifli, Nur Liyana (2023)
The Fourth Industrial Revolution (4IR) has rapidly expanded the use of technology and impacted businesses, including the accounting sector where the role of accounting and duties of accountants are changing quite extensively. In response to this situation, this study aims to identify and analyse the expected information technology (IT) competency of Malaysian accounting graduates in the 4IR. The gap between the job market’s expectations upon accounting graduates’ competency level has led to the formation of IT competency model at the end of the study. In this study, Neo-Correspondence Theory (NCT) is used as a theoretical lens to examine the IT competency amongst accounting graduates and the employers’ expectations in the workplace within the context of 4IR. This study uses a qualitative approach to explore the work environment and IT competency requirements from the perspectives of employers and accounting graduates. The data were collected using semi-structured interviews and documentary reviews and analysed using a thematic analysis approach. This study found that there is a gap between employers’ expectations and accounting graduates’ IT competency concerning the IT competency expected in the 4IR era. Emerging technologies require accounting graduates to have relevant and sufficient IT competencies to ensure their employability.